Lithium-ion secondary battery
By using a binder with high Hansen solubility parameters and an imide-based lithium salt electrolyte in a lithium-ion secondary battery, and predoped lithium ions in the negative electrode, the problem of insufficient heat resistance of lithium ion secondary batteries is solved. It achieves stable operation and high temperature durability under 85℃ environment.
Patent Information
- Application Number
- CN201980029775.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-05-02
- Filing Date
- 2019-04-26
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2039-04-26
AI Technical Summary
The existing lithium-ion secondary batteries have insufficient heat resistance and are difficult to work effectively in an environment of around 85°C, especially in high-temperature applications such as automobiles.
Using a positive electrode binder and a negative electrode binder with a high Hansen solubility parameter RED value greater than 1, combined with an imide-based lithium salt electrolyte, and pre-doped lithium ions in the negative electrode active material to form a stable operation at high temperature. lithium ion secondary battery.
The heat resistance and high-temperature durability of lithium-ion secondary batteries in an environment of 85℃ are achieved, the discharge capacity remains stable, and the internal resistance increases slowly, which significantly improves the service life of the battery at high temperatures.
Smart Images

Figure CN112074985B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a lithium ion secondary battery. Background Art
[0002] Lithium-ion secondary batteries have become increasingly popular due to their excellent properties such as excellent energy density. Moreover, the better the heat resistance of lithium-ion secondary batteries, the wider their applications. Therefore, various technologies for improving the heat resistance of lithium-ion secondary batteries have been proposed. For example, Japanese Patent Publication No. 2014-160638 discloses a lithium-ion secondary battery with heat resistance of about 60°C. Summary of the invention
[0003] However, the heat resistance of the lithium ion secondary battery described in Japanese Patent Application Publication No. 2014-160638 is about 60°C, and a lithium ion secondary battery that can withstand higher temperatures has been sought. For example, in order to use lithium ion secondary batteries in automobiles, heat resistance of about 85°C is required. Therefore, a further improved lithium ion secondary battery is required.
[0004] A feature of the present disclosure is a lithium ion secondary battery comprising: a positive electrode active material capable of absorbing and releasing lithium ions, a positive electrode binder for binding the positive electrode active material, a negative electrode active material capable of absorbing and releasing lithium ions, a negative electrode binder for binding the negative electrode active material, and an electrolyte containing an organic solvent and an imide-based lithium salt, wherein the negative electrode active material is pre-doped with the lithium ions, and the RED value of the positive electrode binder based on the Hansen solubility parameter in the electrolyte is greater than 1.
[0005] According to the above characteristics, the lithium ion secondary battery can have heat resistance of about 85° C. In the present disclosure, the lithium ion secondary battery having heat resistance means having a performance capable of operating in a high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] Figure 1 It is a schematic exploded perspective view of a lithium ion secondary battery according to an embodiment.
[0007] Figure 2 It is a perspective view of a lithium ion secondary battery according to an embodiment.
[0008] Figure 3 yes Figure 2 Schematic diagram of the III-III cross section of a lithium-ion secondary battery.
[0009] Figure 4 Yes Figure 1 FIG. 2 is a diagram for explaining an example of the appearance of a positive electrode plate shown in FIG.
[0010] Figure 5 yes Figure 4 V-V cross-section diagram of the positive plate.
[0011] Figure 6 Yes Figure 1 FIG. 2 is a diagram for explaining an example of the appearance of a negative electrode plate shown in FIG.
[0012] Figure 7 yes Figure 6 VII-VII cross-sectional view of the negative electrode plate.
[0013] Figure 8 Yes Figure 1 A diagram for explaining the positional relationship between a positive electrode plate of a positive electrode, a negative electrode plate of a negative electrode, a separator, and an electrolyte solution shown in FIG.
[0014] Fig. 9 This is a diagram for explaining the upper limit of the pre-doping amount of the negative electrode.
[0015] Fig.10 This is a graph showing the change over time of the internal resistance (mΩ) of the lithium ion secondary battery at 85° C. in Test Example 1.
[0016] Fig.11 This is a graph showing the change over time in the discharge capacity (mAh) of the lithium ion secondary battery at 85° C. in Test Example 1.
[0017] Fig.12 This is a graph showing the change over time of the internal resistance (mΩ) of the lithium ion secondary battery at 85° C. in Test Example 2.
[0018] Fig.13 This is a graph showing the change over time in the discharge capacity (mAh) of the lithium ion secondary battery at 85° C. in Test Example 2.
[0019] Fig.14 This is a graph showing the change over time in the internal resistance of the lithium ion secondary batteries at 85° C. in Test Examples 3 to 5.
[0020] Fig.15 This is a graph showing the change over time in discharge capacity of the lithium ion secondary batteries at 85° C. in Test Examples 3 to 5. DETAILED DESCRIPTION
[0021] The following is an explanation of the embodiments of the present disclosure using the accompanying drawings. Figure 1 As shown in the exploded perspective view of , the lithium-ion secondary battery 1 includes a plurality of plate-shaped positive electrode plates 11 and a plurality of plate-shaped negative electrode plates 21, which are alternately stacked. Each positive electrode plate 11 includes an electrode terminal connection portion 12b protruding in one direction. In addition, each negative electrode plate 21 also includes an electrode terminal connection portion 22b, which protrudes in the same direction as the electrode terminal connection portion 12b of the positive electrode plate 11. Figure 1 As shown, the direction in which the electrode terminal connection portion 12b of the positive electrode plate 11 protrudes is set as the X-axis direction, the stacking direction is set as the Z-axis direction, and the direction orthogonal to the X-axis and the Z-axis is set as the Y-axis direction. These X-axis, Y-axis, and Z-axis are orthogonal to each other. In all figures in which the X-axis, Y-axis, and Z-axis are recorded, these axial directions represent the same direction, and the description of the direction in the following description is sometimes based on these axial directions. It should be noted that in the following description, the illustration and detailed description of the attached structure are omitted.
[0022] <1. Overall structure of lithium-ion secondary battery 1 ( Figure 1 to Figure 3 )>
[0023] like Figure 1 As shown, the lithium ion capacitor 1 includes a plurality of positive electrode plates 11, a plurality of negative electrode plates 21, a plurality of separators 30, an electrolyte 40, and a laminate member 50. Figure 1 As shown, the positive electrode plates 11 and the negative electrode plates 21 are alternately stacked, and the separators 30 are sandwiched between the positive electrode plates 11 and the negative electrode plates 21. The electrolyte 40 is sealed in two laminated components 50 together with a part of the plurality of positive electrode plates 11 stacked in this way, a part of the plurality of negative electrode plates 21, and the plurality of separators 30.
[0024] The electrode terminal connection parts 12b of the plurality of positive electrode plates 11 protrude in the same direction and are connected to the positive electrode terminal 14. The positive electrode terminal 14, the plurality of positive electrode plates 11 connected thereto, and other conductive parts constituting the positive electrode terminal side are collectively referred to as the positive electrode 10. Similarly, the electrode terminal connection parts 22b of the plurality of negative electrode plates 21 are connected to the negative electrode terminal 24, and the negative electrode terminal 24, the plurality of negative electrode plates 21 connected thereto, and other conductive parts constituting the negative electrode terminal side are collectively referred to as the negative electrode 20.
[0025] The lithium ion secondary battery 1 has the above-mentioned structure inside, and its appearance is shown in FIG. Figure 2 .Will Figure 2 The III-III cross section of the lithium ion secondary battery 1 is schematically shown in FIG. Figure 3 . Figure 3 In the figure, for easy understanding, the components in the lithium ion secondary battery 1 are shown with spaces between them. However, in reality, the positive electrode plate 11, the negative electrode plate 21, and the separator 30 are stacked with almost no spaces between them.
[0026] <2. Parts of the lithium-ion secondary battery 1 ( Figure 1 , Figure 3 to Figure 7 )>
[0027] <2-1. Positive plate 11( Figure 1 , Figure 3 to Figure 5 )>
[0028] like Figures 3 to 5As shown, the positive electrode plate 11 includes a thin plate-shaped positive electrode collector 12 and a positive electrode active material layer 13 coated on the positive electrode collector 12. It should be noted that although the positive electrode active material layer 13 is provided on both sides of the positive electrode collector 12, it can also be provided on any single side of the positive electrode collector 12. In addition, in order to prevent the lithium ion secondary battery 1 from containing excessive water, it is necessary to fully dry the coated positive electrode active material layer 13 after applying the positive electrode active material layer 13 to the positive electrode collector 12 during manufacturing.
[0029] The positive electrode current collector 12 is a metal foil having a plurality of holes 12c formed therein that penetrate in the Z direction (see Figure 4 and Figure 5 ), the rectangular collector portion 12a (refer to Figure 4 ) and from one end of the collector 12a ( Figure 4 In the example of FIG. 1 , the electrode terminal connection portion 12 b (the left end of the upper side) protruding outward is formed integrally. Figure 1 and Figure 4 The width of the electrode terminal connection portion 12b in the Y-axis direction shown in FIG. 1 can be appropriately changed, for example, it can be the same width as the current collecting portion 12a. It should be noted that although a plurality of holes 12c are formed in the current collecting portion 12a (see FIG. 1 ), Figure 4 and Figure 5 ), but multiple holes similar to the holes 12c of the collector 12a may not be formed in the electrode terminal connection portion 12b. Here, since the collector 12a has multiple holes 12c, the cations and anions contained in the electrolyte 40 can pass through the collector 12a. It should be noted that multiple holes 12c may not be formed in the collector 12a, and multiple holes similar to the holes 12c may not be formed in the electrode terminal connection portion 12b. The positive electrode collector 12 may be made of a metal foil made of aluminum, stainless steel, copper, or nickel, for example.
[0030] The positive electrode active material layer 13 contains: a positive electrode active material capable of absorbing and releasing lithium ions, and a positive electrode binder that binds the positive electrode active material and binds the positive electrode active material to the collector 12a of the positive electrode collector 12. Thus, the positive electrode active material layer 13 is configured in a manner capable of absorbing and releasing lithium ions by having a positive electrode active material. The positive electrode active material layer 13 may further contain other components such as a conductive auxiliary agent for improving the conductivity of the positive electrode active material layer 13 and a thickening agent for making the positive electrode plate 11 easier to manufacture. The conductive auxiliary agent may be, for example, Ketjen black, acetylene black, graphite particles, and graphite microfibers. The thickening agent may be, for example, carboxymethyl cellulose [CMC].
[0031] The positive electrode active material can use the positive electrode active material that can absorb and release lithium ions used in the previous lithium ion secondary battery. As the positive electrode active material, for example, manganese dioxide (MnO2), iron oxide, copper oxide, nickel oxide, lithium manganese composite oxide (such as Li x Mn2O4 or Li x MnO2), lithium nickel composite oxides (such as Li x NiO2), lithium cobalt composite oxide (Li x CoO2), lithium nickel cobalt composite oxides (such as LiNi 1-y CO y O2), lithium nickel cobalt manganese composite oxide (NMC, ternary system, LiNi x CO y Mn 1-y-z O2), spinel lithium manganese nickel composite oxide (Li x Mn 2-y Ni y O4), lithium polyanion compounds (LiFePO4, LiCoPO4, LiVOPO4, LiVPO4F, LiMnPO4, LiMn 1-x Fe x PO4, LiNiVO4, LiCoPO4, Li3V2(PO4)3, LiFeP2O7, Li3Fe2(PO4)3, Li2CoSiO4, Li2MnSiO4, Li2FeSiO4, LiTePO4, etc.), ferrous sulfate (Fe2(SO4)3), vanadium oxide (e.g. V2O5), etc. In addition, conductive polymer materials such as polyaniline and polypyrrole, disulfide polymer materials, organic materials such as sulfur (S), and fluorinated carbon, and inorganic materials can also be cited. These can be used alone or in combination of two or more.
[0032] The positive electrode active material is preferably a material whose upper limit of the action potential based on Li is less than a predetermined value. Here, in this specification, the action potential based on Li refers to the value of the positive electrode active material relative to the reference potential (Li / Li + ). The prescribed value of the action potential based on Li can be, for example, 5.0 V, 4.0 V, 3.8 V, or 3.6 V. When the prescribed value is 5.0 V, the positive electrode active material having an upper limit of the action potential based on Li of less than 5.0 V can be, for example, spinel lithium manganese nickel composite oxide (Li x Mn 2- y Ni y In addition, when the specified value is 4.0 V, the positive electrode active material whose upper limit of action potential based on Li is less than 4.0 V may include, for example, lithium manganese composite oxide (e.g., Li xMn2O4 or Li x MnO2). In addition, when the specified value is 3.8 V, the upper limit of the action potential based on Li is less than 3.8 V, and examples thereof include lithium cobalt composite oxide (Li x CoO2), lithium nickel cobalt manganese composite oxide (NMC, ternary system, LiNi x CO y Mn 1-y-z O2). In addition, when the predetermined value is 3.6 V, the upper limit of the action potential based on Li is less than 3.6 V, and an example of a positive electrode active material is LiFePO4.
[0033] In particular, when the positive electrode current collector 12 is formed of aluminum, it is preferred to select a positive electrode active material whose upper limit of the action potential based on Li is less than a specified value. If the action potential based on Li of the positive electrode active material is 4.2V or more, the positive electrode current collector 12 formed of aluminum is more likely to corrode during the charge and discharge process. In this case, as the positive electrode active material, for example, LiFePO4 whose upper limit of the action potential based on Li is less than 3.6V can be selected.
[0034] The positive electrode binder can be a binder having a RED value (described later) greater than 1 based on the Hansen solubility parameter in the electrolyte 40 among the binders of the positive and negative electrodes used in the conventional lithium ion secondary batteries. Here, as the binders of the positive and negative electrodes of the conventional lithium ion secondary batteries, for example, polyvinylidene fluoride [PVdF], polytetrafluoroethylene [PTFE], polyvinyl pyrrolidone [PVP], polyvinyl chloride [PVC], polyethylene [PE], polypropylene [PP], ethylene-propylene copolymer, styrene-butadiene rubber [SBR], acrylic resin, polyacrylic acid can be cited.
[0035] In addition, the positive electrode binder has a RED value greater than 1 based on the Hansen solubility parameter (HSP) in the electrolyte 40, and therefore is poorly soluble in the electrolyte 40. The Hansen solubility parameter was published by Charles M Hansen, and is known to be an index of solubility that indicates how much a certain substance dissolves in a certain substance. For example, water and oil are generally immiscible, and this is due to the different "properties" of water and oil. As the "properties" of the substance related to the solubility, the Hansen solubility parameter uses numerical values for each substance to represent the three items of dispersion term D, polarity term P, and hydrogen bond term H. Here, the dispersion term D is a value indicating the magnitude of the van der Waals force, the polarity term P is a value indicating the magnitude of the dipole moment, and the hydrogen bond term H is a value indicating the magnitude of the hydrogen bond. The basic idea is explained below. Therefore, the explanation of the case where the hydrogen bond term H is divided into donor properties and acceptor properties for treatment is omitted.
[0036] In order to study solubility, Hansen solubility parameters (D, P, H) are plotted in a three-dimensional orthogonal coordinate system (Hansen space, HSP space). For example, the Hansen solubility parameters of solution A and solid B can be plotted in the Hansen space at two coordinates (coordinate A, coordinate B) corresponding to solution A and solid B, respectively. Moreover, it can be considered that the shorter the distance Ra (HSP distance, Ra) between coordinate A and coordinate B, the more similar the above-mentioned "properties" of solution A and solid B are to each other, and therefore, solution A is more easily dissolved in solid B. On the contrary, it can be considered that the longer the distance Ra, the more dissimilar the "properties" of solution A and solid B are to each other, and therefore, solid B is less likely to be dissolved in solution A.
[0037] In addition, the boundary between the substance dissolved in solution A and the substance not dissolved in solution A, that is, the distance Ra, is taken as the interaction radius R0. Therefore, for solution A and solid B, when the distance Ra is less than the interaction radius R0 (Ra<R0), it can be considered that solid B is dissolved in solution A. On the other hand, when this Ra is greater than the interaction radius R0 (R0<Ra), it can be considered that solid B is not dissolved in solution A. Furthermore, the value obtained by dividing the distance Ra by the interaction radius R0 is taken as the RED value (=Ra / R0, Relative Energy Difference). In this way, when the RED value is less than 1 (RED=Ra / R0<1), that is, Ra<R0, it can be considered that solid B is dissolved in solution A. On the other hand, when the RED value is greater than 1 (RED=Ra / R0>1), that is, R0<Ra, it can be considered that solid B is not dissolved in solution A. In this way, it is possible to judge whether solid B is dissolved in solution A based on the RED value related to solution A and solid B.
[0038] The electrolyte 40 corresponds to the solution A mentioned here, and the positive electrode binder corresponds to the solid B. Since the positive electrode binder has a RED value based on the Hansen solubility parameter in the electrolyte 40 greater than 1, it is poorly soluble in the electrolyte 40. On the contrary, if the positive electrode binder is poorly soluble in the electrolyte 40 to the extent that the RED value based on the Hansen solubility parameter in the electrolyte 40 is greater than 1, it can be considered that the RED value based on the Hansen solubility parameter of the positive electrode binder is also greater than 1.
[0039] Hansen solubility parameters and interaction radius R0 can be calculated using the chemical structure and composition ratio of the components and experimental results. In this case, they can be obtained using the software HSPiP (Hansen Solubility Parameters in Practice: Windows (registered trademark) software for efficient processing of HSP) developed by Hansen et al. The software HSPiP has been available from http: / / www.hansen-solubility.com / since May 2, 2018. In addition, Hansen solubility parameters (D, P, H) can be calculated even when a mixed solvent containing multiple solvents is used.
[0040] <2-2. Negative plate 21 ( Figure 1 , Figure 3 , Figure 6 , Figure 7 )>
[0041] The negative electrode plate 21 has a structure substantially the same as that of the positive electrode plate 11, and includes a thin plate-shaped negative electrode collector 22 and a negative electrode active material layer 23 coated on the negative electrode collector 22. Although the negative electrode active material layer 23 is coated on both sides of the negative electrode collector 22, the coated side may be any single side. Furthermore, in order to prevent the lithium-ion secondary battery 1 from containing excessive water, after the negative electrode active material layer 23 is coated on the negative electrode collector 22 during manufacturing, it is necessary to fully dry the coated negative electrode active material layer 23. In addition, as described later, the negative electrode active material layer 23 absorbs lithium ions Li during manufacturing. + (so called pre-doping).
[0042] The negative electrode current collector 22 is a metal foil having a plurality of holes 22c extending in the Z direction, similarly to the positive electrode current collector 12 of the positive electrode plate 11 described above (see Figure 6 and Figure 7 ), a rectangular collector portion 22a and a collector portion 22a extending from one end thereof (at Figure 6 The electrode terminal connection portion 22b protruding outward (in the example of the upper right end) is integrally formed. It should be noted that a plurality of holes 22c (see Figure 6 and Figure 7 ), but the electrode terminal connection part 22b may not be formed with a plurality of holes similar to the holes 22c of the collector part 22a, or a plurality of holes similar to the holes 22c may be formed. Here, the collector part 22a is formed with a plurality of holes 22c, so that the cations and anions contained in the electrolyte 40 can pass through the collector part 12a. It should be noted that the collector part 22a may not have a plurality of holes 22c, and the electrode terminal connection part 22b may not have a plurality of holes similar to the holes 22c.
[0043] In addition, if Figure 1As shown, the electrode terminal connection portion 12b of the positive electrode and the electrode terminal connection portion 22b of the negative electrode plate 21 are arranged at positions spaced apart from each other in the surface direction of the negative electrode plate in a non-overlapping manner. Figure 1 and Figure 6 The width of the electrode terminal connection portion 22b in the Y-axis direction can be changed appropriately, for example, it can be the same width as the current collecting portion 22a. The negative electrode current collector 22 can be made of a metal foil such as aluminum, stainless steel, or copper, similar to the positive electrode current collector 12 of the positive electrode plate 11.
[0044] Similar to the above-mentioned positive electrode active material layer 13, the negative electrode active material layer 23 contains a negative electrode active material capable of absorbing and releasing lithium ions, a negative electrode binder that binds the negative electrode active material and binds the negative electrode active material to the collector portion 22a of the negative electrode collector 22. Moreover, the negative electrode active material layer 23 is configured to be capable of absorbing and releasing lithium ions by having a negative electrode active material. The negative electrode active material layer 23 may further contain other components such as a conductive aid for improving the conductivity of the negative electrode active material layer 23 and a thickener for facilitating the manufacture of the negative electrode plate 21. The conductive aid and the thickener may use the same substances as those of the above-mentioned positive electrode plate 11. That is, the conductive aid may use, for example, Ketjen black, acetylene black, graphite particles, and graphite microfibers. The thickener may use, for example, carboxymethyl cellulose [CMC].
[0045] As the negative electrode active material, the negative electrode active material that can absorb and release lithium ions used in the previous lithium ion secondary battery can be used. That is, as the negative electrode active material, for example, carbonaceous materials such as graphite, metal oxides such as tin oxide and silicon oxide, and materials obtained by adding phosphorus and boron to these materials to improve the negative electrode characteristics. In addition, as the negative electrode active material, a material having the chemical formula Li 4+x Ti5O 12 (0≤x≤3) represents lithium titanate having a spinel structure. Here, a material in which a part of Ti is replaced by elements such as Al and Mg can be used. In addition, as the negative electrode active material, silicon-based materials such as silicon, silicon alloys, SiO, and silicon composite materials can also be used. These can be used alone or in combination of two or more.
[0046] The negative electrode binder can use the binder of the positive and negative electrodes used in the conventional lithium ion secondary battery. That is, as the binder of the conventional lithium ion secondary battery, for example, polyvinylidene fluoride [PVdF], polytetrafluoroethylene [PTFE], polyvinyl pyrrolidone [PVP], polyvinyl chloride [PVC], polyethylene [PE], polypropylene [PP], ethylene-propylene copolymer, styrene-butadiene rubber [SBR], acrylic resin, polyacrylic acid can be cited. Such a binder can be used as the negative electrode binder of the lithium ion secondary battery 1.
[0047] The negative electrode active material layer 23 absorbs lithium ions Li during production. + (so called pre-doping).
[0048] There are two main methods for pre-doping. Figure 1 As shown in FIG. 1 , a method is to perform pre-doping inside the laminated component 50, that is, a plurality of positive plates 11, a plurality of negative plates 21, and a plurality of separators 30 are stacked and housed together with the electrolyte 40 inside the laminated component 50 (see FIG. 1 ). Figure 2 Another method is to pre-dope the outside of the laminated component 50, that is, to absorb lithium ions Li in the negative electrode active material before making the negative electrode plate 21. + .
[0049] More specifically, there are two methods for pre-doping the inside of the laminated component 50: a chemical method and an electrochemical method. The method for pre-doping the inside of the laminated component 50 is to accommodate a plurality of positive electrode plates 11, a plurality of negative electrode plates 21, a plurality of separators 30 and an electrolyte 40 in the laminated component 50 (see Figure 2 ) and then pre-doped. The chemical method is to dissolve lithium metal in the electrolyte 40 to convert it into lithium ions Li + And the lithium ion Li + In contrast, in the electrochemical method, a voltage is applied to lithium metal and the negative electrode plate 21 to convert lithium metal into lithium ions Li + And the lithium ion Li + A method of occluding and retaining the negative electrode active material.
[0050] Both the chemical method and the electrochemical method prefer lithium ions Li + The current collecting portion 12a of the positive electrode current collector 12 of the positive electrode plate 11 can be penetrated (see Figure 5 ) and the current collecting portion 22a of the negative electrode current collector 22 of the negative electrode plate 21 (see Figure 7 ) to make lithium ion Li + Therefore, when pre-doping is performed by chemical or electrochemical methods, it is preferred that a plurality of holes 12c are formed in the current collecting portion 12a of the positive electrode plate 11 and a plurality of holes 12c are formed in the current collecting portion 22a of the negative electrode plate 21 (see Figure 7 ) is formed with a plurality of holes 22c.
[0051] On the other hand, the method of pre-doping the outside of the laminated member 50 is to pre-dope the lithium ions Li before the negative electrode plate 21 is manufactured. + The lithium ions Li +Therefore, when the method of pre-doping the outside of the laminated member 50 is used, the plurality of holes 12c may not be formed in the collector 12a of the positive electrode plate 11, and the collector 22a of the negative electrode plate 21 (see Figure 7 ) also does not form multiple holes 22c.
[0052] It should be noted that the method of pre-doping inside the laminated component 50 and the method of pre-doping outside the laminated component 50 can also be appropriately combined. That is, in addition to the method of pre-doping outside the laminated component 50, the pre-doping can also be performed by the following chemical method or electrochemical method: multiple positive electrode plates 11, multiple negative electrode plates 21, multiple separators 30 and electrolyte 40 are accommodated inside the laminated component 50 (see Figure 2 ) after which a method of further pre-doping is performed inside the laminate component 50.
[0053] <2-3. Isolation member 30( Figure 1 , Figure 3 )>
[0054] like Figure 1 As shown, the separator 30 separates the positive electrode plate 11 from the negative electrode plate 21 and is made of a porous material through which cations and anions of the electrolyte 40 can pass, and is formed into a rectangular sheet. Figure 1 and Figure 3 ) is set to be longer than the length of the current collecting portion 12a of the positive electrode current collector 12 of the positive electrode plate 11 (refer to Figure 4 ) and the length of the current collecting portion 22a of the negative electrode current collector 22 of the negative electrode plate 21 (refer to Figure 6 ) is longer. The separator 30 may be a separator used in conventional lithium-ion secondary batteries, for example, paper made of viscose rayon, natural cellulose, or a nonwoven fabric made of polyethylene, polypropylene, or the like.
[0055] <2-4. Electrolyte 40>
[0056] The electrolyte 40 contains an organic solvent (non-aqueous solvent) and an imide-based lithium salt as an electrolyte. An additive may be appropriately added to the electrolyte 40. As an additive, for example, an additive that promotes the formation of a SEI film (Solid Electrolyte Interface) at the negative electrode, such as vinylene carbonate [VC], fluoroethylene carbonate [FEC], ethylene sulfite [ES], etc., may be used.
[0057] As the organic solvent, an organic solvent having a heat resistance of 85°C can be used. For example, carbonate organic solvents, nitrile organic solvents, lactone organic solvents, ether organic solvents, alcohol organic solvents, ester organic solvents, amide organic solvents, sulfone organic solvents, ketone organic solvents, and aromatic organic solvents can be exemplified. One of these organic solvents or a mixture of two or more solvents in an appropriate composition ratio can be used as an organic solvent. Here, as carbonate organic solvents, cyclic carbonates such as ethylene carbonate [EC], propylene carbonate [PC], and fluoroethylene carbonate [FEC], and chain carbonates such as ethyl methyl carbonate [EMC], diethyl carbonate [DEC], and dimethyl carbonate [DMC] can be exemplified. Here, it is preferred that the organic solvent does not contain dimethyl carbonate [DMC], which is a type of chain carbonate. Although dimethyl carbonate [DMC] is rare, it sometimes causes deterioration of heat resistance.
[0058] Examples of nitrile organic solvents include acetonitrile, acrylonitrile, adiponitrile, valeronitrile, and isobutyronitrile. Examples of lactone organic solvents include γ-butyrolactone and γ-valerolactone. Examples of ether organic solvents include tetrahydrofuran, dihydrofuran, and isobutylene glycol. Cyclic ethers such as alkane, chain ethers such as 1,2-dimethoxyethane, dimethyl ether, and triethylene glycol dimethyl ether. In addition, as alcohol organic solvents, ethanol and ethylene glycol can be exemplified. In addition, as ester organic solvents, phosphates such as methyl acetate, propyl acetate, and trimethyl phosphate, sulfates such as dimethyl sulfate, and sulfites such as dimethyl sulfite can be exemplified. As amide organic solvents, N-methyl-2-pyrrolidone and ethylenediamine can be exemplified. As sulfone organic solvents, chain sulfones such as dimethyl sulfone and cyclic sulfones such as 3-cyclobutene sulfone can be exemplified. As ketone organic solvents, methyl ethyl ketone can be exemplified, and as aromatic organic solvents, toluene can be exemplified. Moreover, the above-mentioned various organic solvents other than carbonate organic solvents are preferably used in a mixed cyclic carbonate, and are particularly preferably used in a mixed manner with ethylene carbonate [EC] that can form a SEI film (Solid Electrolyte Interface) at the negative electrode. In this case, the above-mentioned positive electrode binder and negative electrode binder are preferably polyacrylic acid. In addition, the organic solvent preferably contains ethyl methyl carbonate [EMC] and diethyl carbonate [DEC].
[0059] The electrolyte may use an imide-based lithium salt (a lithium salt having -SO2-N-SO2- in its partial structure). Here, as imide-based lithium salts, examples include lithium bis(fluorosulfonyl)imide [LiN(FSO2)2, LiFSI], lithium bis(trifluoromethanesulfonyl)imide [LiN(SO2CF3)2, LiTFSI], and lithium bis(pentafluoroethanesulfonyl)imide [LiN(SO2CF2CF3)2, LiBETI]. As the electrolyte, only one of these imide-based lithium salts may be used, or two or more of them may be mixed and used. These imide-based lithium salts have a heat resistance of 85°C. Even when an imide-based lithium salt (e.g., lithium bis(fluorosulfonyl)imide [LiN(FSO2)2, LiFSI]) without a trifluoromethane group (-CF3), a pentafluoroethane group (-CF2CF3), or a pentafluorophenyl group (-C6F5) is used among the above-mentioned imide-based lithium salts, it is preferred for the following reasons. That is, the positive electrode binder and the negative electrode binder have a tendency that the RED value based on the Hansen solubility parameter becomes greater than 1. In addition, the ion conductivity of the electrolyte 40 is not easily reduced at high temperatures or low temperatures, and the electrolyte 40 is stable.
[0060] The concentration of the electrolyte in the electrolyte solution 40 is preferably 0.5 to 10.0 mol / L. From the viewpoint of the appropriate viscosity and ion conductivity of the electrolyte solution 40, the concentration of the electrolyte in the electrolyte solution 40 is more preferably 0.5 to 2.0 mol / L. When the concentration of the electrolyte is less than 0.5 mol / L, the ion conductivity of the electrolyte solution 40 is too low due to the decrease in the concentration of ions dissociated from the electrolyte, which is not preferred. In addition, when the concentration of the electrolyte is greater than 10.0 mol / L, the ion conductivity of the electrolyte solution 40 is too low due to the increase in the viscosity of the electrolyte solution 40, which is not preferred. In addition, when the electrolyte solution 40 containing the above organic solvent and electrolyte is used, the above-mentioned positive electrode binder and negative electrode binder are preferably polyacrylic acid.
[0061] <2-5. Laminated component 50 ( Figure 1 , Figure 3 )>
[0062] like Figure 3 As shown, the laminated component 50 includes a core sheet 51, an outer sheet 52, and an inner sheet 53. The outer sheet 52 is bonded to the outer surface of the core sheet 51, and the inner sheet 53 is bonded to the inner surface of the core sheet 51. For example, the core sheet 51 may be an aluminum foil, the outer sheet 52 may be a resin sheet such as a nylon polyester film or a PET film, and the inner sheet 53 may be a resin sheet such as a polypropylene.
[0063] <3. The charging and discharging process of the lithium-ion secondary battery 1 ( Figure 3 , Figure 8 , Fig. 9 )>
[0064] The positional relationship between the positive electrode plate 11 of the positive electrode 10, the negative electrode plate 21 of the negative electrode 20, the separator 30, and the electrolyte 40 of the lithium ion secondary battery 1 (see Figure 1 ) is schematically shown in Figure 8 .like Figure 8 As shown in the figure, the lithium ion secondary battery 1 is formed by a positive electrode plate 11 and a negative electrode plate 21 facing each other with a separator 30 sandwiched therebetween. As described above, both the positive electrode active material layer 13 and the negative electrode active material layer 23 are capable of absorbing and releasing lithium ions Li + way of composition.
[0065] In the lithium ion secondary battery 1 during charging, the lithium ions Li stored in the positive electrode active material layer 13 + The lithium ions Li in the electrolyte 40 are released into the electrolyte 40 in an amount equal to the lithium ions Li + stored in the negative electrode active material layer 23 (see Figure 8 and Fig. 9 ). On the other hand, in the lithium ion secondary battery 1 during discharge, the lithium ions Li stored in the negative electrode active material layer 23 + The lithium ions Li in the electrolyte 40 are released into the electrolyte 40, and the lithium ions Li in the electrolyte 40 are equal to the lithium ions Li in the electrolyte 40. + The positive electrode active material layer 13 is stored. As if during the charge and discharge process, lithium ions Li + The electrolyte 40 is interposed between the positive electrode active material layer 13 and the negative electrode active material layer 23 (see Figure 8 and Fig. 9 ) moves. That is, lithium ions Li + The electrolyte 40 moves from the positive electrode active material layer 13 to the negative electrode active material layer 23 during charge, and moves from the negative electrode active material layer 23 to the positive electrode active material layer 13 during discharge (see Figure 8 and Fig. 9 Then, the lithium ions Li 2 are stored in the negative electrode active material layer 23. + The maximum amount of Li+ is reached when the battery is fully charged during the charge and discharge process. + The lithium ions Li stored in the positive electrode active material layer 13 and the negative electrode active material layer 23 are + It should be noted that in this specification, lithium ion Li + As long as the amount of lithium ions Li + Any value that is proportional to the number of atoms may be used, for example, the number of mol.
[0066] <4. Pre-doping>
[0067] The negative electrode active material layer 23 is pre-doped with lithium ions Li + , the pre-doped lithium ion Li +The amount may also be set with an upper limit as described below.
[0068] All the lithium ions Li stored in the positive electrode active material layer 13 during full discharge + The amount of Pt is equivalent to the amount of lithium ions Li + When the state changes from a fully discharged state to a fully charged state, the negative electrode active material layer 23 (see Fig. 9 Here, the lithium ions Li stored in the negative electrode active material layer 23 during full charge are + The amount N is the amount of lithium ions Li that move from the positive electrode active material layer 13 to the negative electrode active material layer 23. + The amount of Pt and the lithium ions Li occluded in the negative electrode active material layer 23 during pre-doping + The sum of the quantity Np is Np+Pt (refer to Fig. 9 Here, Pt represents all the lithium ions Li 2 stored in the positive electrode active material layer 13 during full discharge. + The amount of lithium ions Li + The inactive compound may also be formed by the lithium ions Li ions occluded in the negative electrode active material layer 23 during the pre-doping. + Therefore, Pt is the same as the lithium ions Li occluded in the positive electrode active material layer 13 before the initial charge. + The amount of lithium ions Li occluded by the positive electrode active material before production (i.e., the amount of lithium ions Li + The amount of ) is equal to the amount.
[0069] Furthermore, the lithium ions Li that can be stored in the negative electrode active material layer 23 before pre-doping are + The amount is set to Nt (refer to Fig. 9 As described above, when fully charged, the lithium ions Li stored in the negative electrode active material layer 23 + The amount N is Np+Pt (i.e., the lithium ions Li 20 stored in the negative electrode active material layer 23 during pre-doping). + The amount Np is related to the amount of lithium ions Li that move from the positive electrode active material layer 13 to the negative electrode active material layer 23 during full discharge to full charge. + The sum of the amount Pt) (refer to Fig. 9 ).
[0070] When the lithium ions Li are stored in the negative electrode active material layer 23 during full charge, + The amount N (=Np+Pt) exceeds the amount of lithium ions Li that can be absorbed by the negative electrode active material layer 23 before pre-doping. +In the case of the amount Nt (i.e., Np+Pt>Nt), the excess portion (i.e., Np+Pt-Nt) cannot be completely absorbed into the negative electrode active material layer 23, and thus may be precipitated in the electrolyte 40 as lithium metal. Therefore, the lithium ions Li absorbed into the negative electrode active material layer 23 during pre-doping can be + The amount Np is set to an upper limit Npmax, that is, Npmax = Nt-Pt. Thus, Np + Pt ≤ Nt, which can make the negative electrode active material layer 23 always absorb the lithium ions Li released from the positive electrode active material layer 13. + , which can inhibit the lithium ion Li + It should be noted that Npmax, Nt, and Pt can be expressed by the number of mol or the like.
[0071] Here, as described above, Pt is a lithium ion Li stored in the positive electrode active material layer 13 before initial charge. + The amount of lithium ions Li occluded by the positive electrode active material before production (i.e., the amount of lithium ions Li + Therefore, the lithium ions Li 23 absorbed into the negative electrode active material layer 23 during the pre-doping are equal to the amount of + The upper limit Npmax of the amount of lithium ions Li that can be absorbed by the negative electrode active material layer 23 before pre-doping is + The amount of lithium ions Li absorbed by the positive electrode active material before production is subtracted from the amount Nt + Nt and Pt can be calculated from the theoretical values of the positive electrode active material and the negative electrode active material, for example. In addition, the amount of lithium ions Li that can be absorbed by the negative electrode active material before pre-doping can also be measured in an experiment. + The amount of lithium ions Li absorbed by the positive electrode active material + The amount is calculated from its measured value.
[0072] As described above, the lithium ions Li occluded in the negative electrode active material layer 23 during the pre-doping + The upper limit value Npmax of the amount Np is Npmax = Nt - Pt. Therefore, Npmax varies according to the value of Nt and the value of Pt (refer to Fig. 9 ). Generally speaking, the larger the value of Nt, the larger the Npmax, and the larger the value of Pt, the smaller the Npmax (refer to Fig. 9 For example, when Nt is twice as large as Pt (i.e., Nt = 2·Pt), Npmax is equal to Pt (refer to Fig. 9 ). In addition, for example, when Nt is three times Pt (i.e., Nt=3·Pt), Npmax is equal to two times Pt (i.e., 2·Pt) (refer to Fig. 9 ). Thus, Npmax varies according to the value of Nt and the value of Pt (refer to Fig. 9 That is, the lithium ions Li occluded in the negative electrode active material layer 23 during the pre-doping+ The upper limit value Npmax of the amount Np is determined by the amount of lithium ions Li that can be stored in the negative electrode active material layer 23 before pre-doping. + The amount Nt and the lithium ions Li stored in the positive electrode active material layer 13 before charge and discharge + The amount Pt varies.
[0073] In addition, as described above, the lithium ions Li 24 stored in the negative electrode active material layer 23 during the pre-doping process are + The amount Np of the negative electrode active material layer 23 is set to an upper limit Npmax, that is, Npmax = Nt - Pt can also be explained as follows. + The amount of lithium ions Li 23 absorbed into the negative electrode active material layer 23 during full charge is the largest, that is, during full charge. + The amount N is the total amount of lithium ions Li stored in the positive electrode active material layer 13 during full discharge. + The amount of Pt and the lithium ions Li occluded in the negative electrode active material layer 23 during pre-doping + The sum of the quantities Np and Np+Pt (i.e., N=Np+Pt) (refer to Fig. 9 ). The lithium ions Li occluded in the negative electrode active material layer 23 during pre-doping + When the amount Np reaches the upper limit Npmax (Np=Npmax=Nt-Pt), the lithium ions Li 2 stored in the negative electrode active material layer 23 during full charge are + The quantity N (=Np+Pt) is N=Np+Pt=Nt-Pt+Pt=Nt.
[0074] Here, the lithium ions Li stored in the negative electrode active material layer 23 during full charge are + The amount N (refer to Fig. 9 ), the lithium ions Li that can be absorbed by the negative electrode active material layer 23 before pre-doping + When the amount Nt is 100%, and N is expressed in %, when N=Nt, N is 100%. As described above, the lithium ions Li 20 stored in the negative electrode active material layer 23 by pre-doping are + When the amount Np of the negative electrode active material layer 23 is equal to the upper limit Npmax (Np=Npmax=Nt-Pt), the lithium ions Li stored in the negative electrode active material layer 23 during full charge are + The amount N(=Np+Pt) is N=Nt, so N=100%. As described above, the lithium ions Li stored in the negative electrode active material layer 23 + The maximum value of the amount of is N (=Np+Pt) at full charge. Therefore, the lithium ions Li ions stored in the negative electrode active material layer 23 by pre-doping are +When the amount Np of the negative electrode active material layer 23 is equal to the upper limit Npmax (Np=Npmax=Nt-Pt), the lithium ions Li 20 stored in the negative electrode active material layer 23 are + The maximum amount of N is 100%, and does not exceed 100%. That is, by the lithium ions Li occluded in the negative electrode active material layer 23 by pre-doping + The amount Np of the negative electrode active material layer 23 is set to an upper limit Npmax (=Nt-Pt), so that the lithium ions Li 23 are stored in the negative electrode active material layer 23. + The amount of Li is always adjusted during the charge and discharge process to the amount of lithium ions Li that can be absorbed by the negative electrode active material layer 23 before pre-doping. + The doping rate of the negative electrode active material in the negative electrode active material layer is expressed as follows.
[0075] Doping rate (%) = N / Nt × 100
[0076] N: The amount of lithium ions absorbed by the negative electrode active material (negative electrode active material layer) when fully charged (mol)
[0077] Nt: The amount of lithium ions absorbed by the negative electrode active material (negative electrode active material layer) before pre-doping (mol)
[0078] [Another embodiment]
[0079] As another embodiment, for example, the above-mentioned lithium ion secondary battery is a stacked lithium ion secondary battery obtained by stacking the positive electrode plate 11, the negative electrode plate 21 and the separator 30, but it can also be a wound lithium ion secondary battery obtained by winding a long positive electrode, a long negative electrode and a long separator.
[0080] The lithium ion secondary battery may be a lithium polymer secondary battery.
[0081] 《Heat resistance of lithium-ion secondary batteries》
[0082] According to the configuration described above, the lithium ion secondary battery 1 has a heat resistance of 85°C.
[0083] In addition, when the conventional lithium-ion secondary battery is kept at about 85°C, the lithium ion Li + Lithium ions that slowly become inactive compounds and can participate in charge and discharge + The amount of charge and discharge capacity decreases slowly, and sometimes the charge and discharge capacity decreases slowly. Such a lithium-ion secondary battery has a slowly decreasing charge and discharge capacity at high temperatures, that is, it lacks high-temperature durability. In this specification, high-temperature durability means that the charge and discharge capacity of the lithium-ion secondary battery can be maintained at a sufficient amount over time even at high temperatures.
[0084] In contrast, the lithium ion secondary battery 1 has lithium ions Li pre-doped in the negative electrode active material. + , lithium ion Li + Therefore, even if the lithium ions Li required for charging and discharging are + It can also be transformed into an inactive compound by absorbing lithium ions Li pre-doped into the negative electrode active material. + The change is compensated to suppress the decrease in the charge and discharge capacity of the lithium ion secondary battery 1. Therefore, the lithium ion secondary battery 1 has not only heat resistance of 85°C but also high high temperature durability.
[0085] In addition, when lithium-ion secondary batteries are used for a long time in a high temperature environment, the discharge capacity decreases and the internal resistance increases. However, as the doping rate increases, there is a trend that the rate of decrease in discharge capacity and the rate of increase in internal resistance decrease. Therefore, the doping rate is preferably 50% to 100%, more preferably 80% to 100%, and further preferably 90% to 100%.
[0086] The lithium ion secondary battery of the present disclosure is not limited to the structure, configuration, appearance, shape, etc. described in the above embodiments, and various changes, additions, and deletions can be made by understanding the above embodiments.
[0087] Hereinafter, the technology of the present disclosure will be described in more detail with reference to test examples, but the technology of the present disclosure is not limited to these scopes.
[0088] <Manufacturing of lithium-ion secondary batteries>
[0089] [Production of positive electrode]
[0090] First, a positive electrode slurry containing a positive electrode active material is prepared using 88 parts by mass of LiFePO4 as a positive electrode active material, 6 parts by mass of polyacrylic acid (sodium neutralized salt of polyacrylic acid) as a binder, 15 parts by mass of carbon black as a conductive aid, 0.3 parts by mass of carboxymethyl cellulose as a thickener, and 217 parts by mass of water as a solvent.
[0091] The positive electrode slurry was prepared according to the following procedure.
[0092] (1) All materials and water were mixed using a mixer a (Defoaming Rentaro ARE-310 manufactured by THINKY Co., Ltd.) to prepare a pre-slurry.
[0093] (2) The pre-slurry obtained in (1) was further mixed with a mixer b (FILMIX 40-L manufactured by PRIMIX Corporation) to prepare an intermediate slurry.
[0094] (3) The intermediate slurry obtained in (2) was mixed again using the mixer a to prepare a positive electrode slurry A.
[0095] Next, a 15 μm thick aluminum foil (porous foil) was used as a current collector foil, and the positive electrode slurry was applied to the current collector foil and dried to prepare a positive electrode. The amount of positive electrode slurry applied was 3 mg / cm2 based on the mass of the activated carbon after drying. 2 The positive electrode slurry is applied to the collector foil using a blade coater or a die coater.
[0096] [Preparation of negative electrode]
[0097] 98 parts by mass of graphite as a negative electrode active material, 1.4 parts by mass of styrene butadiene rubber (SBR) as a binder, 0.7 parts by mass of carboxymethyl cellulose as a thickener, and 96 parts by mass of water as a solvent were mixed to prepare a negative electrode slurry in the following procedure.
[0098] (1) Materials other than the binder and water are mixed using a mixer a to prepare a pre-slurry.
[0099] (2) The pre-slurry obtained in (1) is further mixed with a mixer b to prepare an intermediate slurry.
[0100] (3) A binder is added to the intermediate slurry obtained in (2), and the mixture is mixed using a mixer a to prepare a negative electrode slurry.
[0101] Next, a copper foil (porous foil) with a thickness of 10 μm was used as a current collector foil, and the negative electrode slurry was applied to the current collector foil and dried to prepare a negative electrode. The amount of negative electrode slurry applied was 3 mg / cm based on the mass of the dried graphite. 2 A blade coater was used to coat the negative electrode slurry on the collector foil.
[0102] [Preparation of electrolyte]
[0103] To a mixed solvent containing 20.0 vol% of ethylene carbonate [EC], 10.0 vol% of propylene carbonate [PC], 46.7 vol% of ethyl methyl carbonate [EMC], and 23.3 vol% of diethyl carbonate [DEC], lithium bis(fluorosulfonyl)imide [LiN(FSO2)2, LiFSI], which is an imide-based lithium salt, was added as an electrolyte. The electrolyte contained 1.0 mol / L of LiFSI.
[0104] [Assembly of lithium-ion secondary batteries]
[0105] A lithium ion secondary battery was produced according to the following procedure.
[0106] (1) The positive electrode and the negative electrode were punched out into rectangles of 60 mm × 40 mm in size, with 40 mm × 40 mm of coating remaining. The coating of a 20 mm × 40 mm region at one end of the long side was peeled off to attach a current collecting terminal.
[0107] (2) A laminate was prepared by placing the coating film portions of the positive electrode and the negative electrode facing each other with a 20 μm thick fiber separator interposed therebetween.
[0108] (3) The stacked body prepared in (2) and the metal lithium foil for lithium pre-doping are wrapped in an aluminum laminate foil, and an electrolyte is injected and sealed to produce a lithium ion capacitor.
[0109] The RED value of the positive electrode binder in the electrolyte was calculated and confirmed to be greater than 1.
[0110] The lithium ion secondary battery was pre-doped to prepare the lithium ion secondary battery of Experimental Example 1. + According to the literature value, the number of moles of lithium ions Li 2+ stored in the positive electrode active material layer is + The amount of Li is 0.0010 mol, and the negative electrode active material layer can absorb lithium ions Li + In addition, in the pre-doping, 0.0102 g of metallic lithium was dissolved in the electrolyte, thereby causing 0.0015 mol of lithium ions Li to be absorbed in the negative electrode active material layer. + It should be noted that the lithium ion secondary battery of Test Example 2 differs from the lithium ion secondary battery of Test Example 1 only in that no pre-doping is performed.
[0111] Using the lithium ion secondary batteries of Test Examples 1 and 2, the following tests were performed.
[0112] [Battery performance measurement]
[0113] The internal resistance and discharge capacity of the lithium ion secondary battery were measured at room temperature (25° C.) at a cutoff voltage of 3.0 to 3.5 V, a measuring current of 5 mA, and 0.2 C. Here, the internal resistance was measured by the DC-IR method to measure the internal resistance (mΩ) at 0 to 0.1 sec.
[0114] [Durability test (85℃ floating charge test)]
[0115] A lithium-ion secondary battery connected to an external power source and maintained at a voltage of 3.5 was placed in a thermostatic chamber at 85°C. The placement time was equivalent to the floating charge time at 85°C and 3.5V. After the specified time, the lithium-ion secondary battery was taken out of the thermostatic chamber and returned to room temperature before the above battery performance measurement was performed.
[0116] [Measurement results]
[0117] The change in internal resistance (mΩ) of the lithium ion secondary battery of Test Example 1 over time is shown in FIG. Fig.10 The time-dependent change of discharge capacity (mAh) is shown in Fig.11 In addition, the time-dependent change in the internal resistance (mΩ) of the lithium ion secondary battery of Test Example 2 is shown in FIG. Fig.12 The time-dependent change of discharge capacity (mAh) is shown in Fig.13 .
[0118] like Fig.10 As shown in FIG. 1 , the internal resistance (mΩ) of the lithium ion secondary battery of Test Example 1 did not increase significantly even after 400 hours. Fig.11 As shown, the discharge capacity (mAh) of the lithium ion secondary battery of Test Example 1 did not significantly decrease even after 400 hours. Therefore, it was confirmed that the lithium ion secondary battery of Test Example 1 had heat resistance at 85° C. and high temperature durability.
[0119] like Fig.12 As shown in FIG. 2 , the internal resistance (mΩ) of the lithium ion secondary battery of Test Example 2 did not increase significantly even after 400 hours. Fig.13 As shown, the discharge capacity (mAh) of the lithium ion secondary battery of Test Example 2 decreases with time. This shows that the lithium ion secondary battery of Test Example 2 has heat resistance that allows it to operate in an environment of 85°C, but its high temperature durability is lower than that of Test Example 1.
[0120] <Study on the influence of doping rate>
[0121] Next, the influence of the doping rate of lithium ions was studied. The lithium ion secondary batteries of Experimental Examples 3 to 5 were prepared by the above-mentioned manufacturing method, and the following tests were performed. The doping rate of Experimental Example 3 was adjusted to 80%, the doping rate of Experimental Example 4 was adjusted to 90%, and the doping rate of Experimental Example 5 was adjusted to 100%.
[0122] [Float charge test]
[0123] The internal resistance and discharge capacity of the lithium-ion secondary battery were measured at room temperature (25°C) with a cutoff voltage of 3.0 to 3.5V, a measuring current of 5mA, and 0.2C. The internal resistance was measured by measuring the internal resistance (mΩ) at 0 to 0.1sec using the DC-IR method. Next, the lithium-ion secondary battery, which was connected to an external power supply and maintained at a voltage of 3.8V, was placed in a thermostatic chamber at 85°C. After a specified time, the lithium-ion secondary battery was taken out of the thermostatic chamber and the above-mentioned battery performance was measured after returning to room temperature. Fig.14 The increase rate of the internal resistance of Test Examples 3 to 5 is shown in FIG. Fig.15 Changes in discharge capacity of Test Examples 3 to 5 are shown in FIG.
[0124] like Fig.14 As shown in Figure 2, the internal resistance increase rate of the lithium ion secondary batteries of Test Examples 3 to 5 was less than 50% even after 1600 hours. Fig.15 As shown, the capacity retention rate of the lithium ion secondary batteries of Test Examples 3 to 5 is 85% or more even after 1600 hours. Therefore, it is shown that the lithium ion secondary batteries of Test Examples 3 to 5 have heat resistance and high temperature durability at 85°C. In addition, Test Examples 4 and 5 are better than the results of Test Example 3 in the increase rate of internal resistance and the change of discharge capacity. Therefore, it can be seen that the doping rate is preferably 90 to 100% compared to 80%.
[0125] <Study on the impact on RED value>
[0126] Next, the influence of the RED value was examined. It should be noted that in the production of the lithium ion secondary battery, only the positive electrode and the electrolyte were changed from the above method, so only these changes will be described below, and repeated descriptions will be omitted.
[0127] [Production of positive electrode]
[0128] Using LiFePO4 as a positive electrode active material, polyacrylic acid (sodium neutralized salt of polyacrylic acid), acrylate or styrene-butadiene [SBR] as a binder, acetylene black as a conductive aid, carboxymethyl cellulose [CMC] as a thickening material, and water as a solvent, the positive electrode slurries A to C containing the positive electrode active material were adjusted by the above method according to the composition shown in Table 1. It should be noted that "parts" in Table 1 represent mass parts, and "%" represents mass %.
[0129] [Table 1]
[0130]
[0131] [Adjustment of electrolyte]
[0132] As a solvent, a mixed solvent of 30 vol% ethylene carbonate (EC), 30 vol% dimethyl carbonate (DMC) and 40 vol% ethyl methyl carbonate (EMC) was used, and 1 mol / L of lithium bis(fluorosulfonyl)imide (LiFSI) was added to the mixed solvent to adjust the electrolyte I. In addition, lithium hexafluorophosphate (LiPF6) was added to the mixed solvent to adjust the electrolyte P. In addition, as a solvent, a mixed solvent of 30 vol% ethylene carbonate (EC), 46.7 vol% ethyl methyl carbonate (EMC), 23.3 vol% diethyl carbonate (DEC), and 10 vol% propylene carbonate (PC) was used, and 1 mol / L of lithium bis(fluorosulfonyl)imide (LiFSI) was added to the mixed solvent to adjust the electrolyte I2.
[0133] [Assembly of lithium-ion secondary batteries]
[0134] Lithium ion secondary batteries of Test Examples 6 to 10 were prepared using the combinations of positive electrodes and electrolyte solutions shown in Table 2. Table 2 also shows the RED values of the respective combinations.
[0135] [Table 2]
[0136] Positive electrode (binder) Electrolyte RED value Test Example 6 A(Polyacrylic acid) 1(LiFSI) 2.48 Test Example 7 A(Polyacrylic acid) 12(LiFSI) Greater than 1 Test Example 8 B(Acrylate) 1(LiFSI) 0.21 Test Example 9 C(SBR) 1(LiFSI) 0.61 Test Example 10 C(SBR) <![CDATA[P(LiPF6)]]> 0.61
[0137] [Determination of initial performance]
[0138] The lithium ion secondary batteries of Test Examples 6 to 10 were pre-doped with lithium, charged and discharged, and aged. Afterwards, the internal resistance and discharge capacity of each lithium ion secondary battery were measured at room temperature (25°C) with a cutoff voltage of 2.2 to 3.8 V and a measuring current of 10C, and the results were used as initial performance. It should be noted that the doping rate was adjusted to 80%.
[0139] [Durability test (85℃ floating charge test)]
[0140] The lithium-ion secondary batteries of Test Examples 6 to 10 were placed in a thermostatic chamber at 85°C while connected to an external power supply and maintaining the voltage at 3.8V. The placement time is equivalent to the floating charge time at 85°C and 3.8V. After the specified time, the lithium-ion secondary batteries were taken out of the thermostatic chamber, and after returning to room temperature, the internal resistance and discharge capacity were measured under the same conditions as the above-mentioned initial performance measurement, and the capacity retention rate (the percentage of the discharge capacity when the initial discharge capacity is set to 100%) and the internal resistance increase rate (the increase rate of the internal resistance from the initial performance) were calculated. The results are shown in Table 3.
[0141] [Table 3]
[0142]
[0143] According to Table 3, when placed in a high temperature environment of 85°C, the capacity retention rate in Test Example 10 using an electrolyte containing fluorolithium phosphate instead of an imide-based lithium salt as an electrolyte was halved in a short period of time. In contrast, the capacity retention rate in Test Examples 6 to 9 using an electrolyte containing an imide-based lithium salt as an electrolyte remained high for a long time. However, even when an electrolyte containing an imide-based lithium salt as an electrolyte was used, the internal resistance increase rate differed due to the composition of the binder of the positive electrode. Therefore, the RED values of the polymer constituting the binder of the positive electrode in the electrolyte (see Table 2) were compared, and the results showed that the internal resistance increase rate was higher in Test Example 8 using an acrylate with a RED value of less than 1 and Test Example 9 using SBR. In contrast, in Test Examples 6 and 7, an electrolyte containing an imide-based lithium salt as an electrolyte was used, and as a polymer constituting the binder of the positive electrode, polyacrylic acid with a RED value greater than 1 in the electrolyte was used. In this case, it is found that the polymer constituting the binder of the positive electrode is not easily dissolved in the electrolyte, and the capacity retention rate is kept high even when left in a high temperature environment of 85° C., and the internal resistance increase rate is suppressed to be small.
Claims
1. A lithium-ion secondary battery comprising: The positive electrode active material can absorb and release lithium ions. A positive electrode binder is used to bind the positive electrode active material. Negative electrode active material, which can absorb and release lithium ions, A negative electrode binder to bind the negative electrode active material, and The electrolyte comprises an organic solvent and an imide-based lithium salt, The organic solvent contains ethylene carbonate, ethyl methyl carbonate, diethyl carbonate and propylene carbonate. The organic solvent does not contain dimethyl carbonate, The negative electrode active material is pre-doped with the lithium ions, The RED value of the positive electrode binder based on the Hansen solubility parameter in the electrolyte is greater than 1, The doping rate of the negative electrode active material is 90% to 100%, and the doping rate is expressed by the following formula: Doping rate (%) = N / Nt × 100, N: The amount of lithium ions absorbed by the negative electrode active material when fully charged, in mol. Nt: The amount of lithium ions absorbed by the negative electrode active material before pre-doping, in mol.
2. The lithium ion secondary battery according to claim 1, wherein The upper limit of the action potential of the positive electrode active material based on Li is less than 5.0 V.
3. The lithium ion secondary battery according to claim 1 or 2, wherein: At least one of the positive electrode binder and the negative electrode binder is polyacrylic acid.
Citation Information
Patent Citations
Binder for battery electrode, electrode using the same, and battery
JP2014160638A
Lithium ion capacitor
JP2017017299A